NICPRINT-50, Being some account of the history of the printing, packaging and newspaper industry of South Africa, and of the National Industrial Council for Printing, prepared to mark the Jubilee of the Council 1919-1969 - Picton, L J (School of Economics, 2018)
The National Industrial Council of the Printing and Newspaper Industry of South Africa celebrates its Golden Jubilee in 1969 and this thesis was undertaken primarily to examine and record the Socio-economic effects of its work. To set the achievements of the Council in perspective it was proposed to preface the record with a brief sketch of the industry itself, but what was intended as an introduction has grown into a major part of the finished work which therefore contains more history and less economics than originally planned. It is hoped that the work will be no less acceptable for this change of emphasis.